PERKEMBANGAN OJEK ONLINE DIKOTA BANJARMASIN - Widarto Widarto; Rijalul Gadi; Singgih Priono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The purpose of the research is to know the development of Ojek line, knowing the factors that inhibit the development of Ojek on line and to know the factors that support the development of Ojek on line in Banjarmasin CityThis research uses descriptive methods. Key informant in this case is the employee who came from the Department of Communication and Informatics of Banjarmasin City, while the informant is the users of taxi services on line and the perpetrator Ojek on line. To sharpen research derived from two sources, sourced from primary data, primary data obtained from interviews with key informant and informant, so that the data according to the problems studied, the second source is the data seconder. Development on line Ojek in the city of Banjarmasin has increased year after year, nevertheless the Ojek on line is still not fully handled by the Office of Communication and Informatics communications, so that there is no accurate data Number of Ojek on line this.The supporting factor of the existence of the Ojek on line is seen from several aspects, namely from the economic aspects, Ojek on line Create new jobs, so as to increase the income of members of the community, in terms of social, ojek on line will Reducing unemployment rate, reducing traffic flow congestion. In terms of law, there are legislation that is used as the basis for the operation of Ojek on line.The factor that has taken the development of Ojek on line is seen in terms of legal aspects is the absence of regional regulations that can be used as a reference to act on Ministerial Regulation 108 year 2017 on the transport of people Transportation Public motor is not on the route, including instructions and technical instructions, in addition, also comes from members of the community who still use the traditional ojek, so that the Ojek on line is not moving freely. Keywords: Developing, transportation online